Kampanye Kesehatan Mental Melalui Meme: Edukasi Komunikasi Asertif di Kalangan Siswa SMAN 6 Kota Tangerang - Wininda Qusnul Khotimah; Vilya Dwi Agustini; Andys Tiara (UII, 2022)
Mental health is currently an issue that gets more attention at a young age. The age at which identity and character are still in the process of being formed. Students need information related to assertive communication, by better understanding assertive communication immediately negative adolescent behavior such as violence, drugs, free sex can be avoided. Especially during the pandemic, the use of social media is increasing, the practice of bullying via social media is one of the problems that are often encountered among teenagers. Using online methods via zoom meetings, education on assertiveness and training in making memes, they were chosen as material for their mental health care campaign that they can use on social media.